Comparison of Sexual Behavior and Inflammatory Parameters in Prostate Cancer Patients with Control Group: Prospective Controlled Study: Effect of Sexual Behavior on Prostate Cancer - Benli, Erdal; Yuce, Ahmet; Cirakoglu, Abdullah; Yazici, Ibrahim; Nalbant, Ismail (Urology Journal, 2021)
Purpose: In spite of extraordinary developments in diagnostic and treatment methods for prostate cancer (PCa), the reason for this disease is not known. Our study aimed to compare men in the PCa group with a control group in terms of sexual behavior like partner numbers and ejaculation frequency, and inflammatory parameters examined in serum. Material and Methods: This study was performed prospectively between 2013 and April 2020 and the record system was kept by a single doctor. Patients were prospectively recorded by a single person. Patients with diagnosis of PCa were compared with a control group in terms of sexual behavior and in terms of inflammatory parameters like neutrophil lymphocyte ratio (NLR, neutrophil count/lymphocyte count), systemic inflammatory index (SII, neutrophil count x platelet count/lymphocyte count). Results: In this study, median marriage age was 18 ± 6 years in the control group and 20 ± 2.97 in the PCa group (P = .001). The median lifelong partner number was observed to be 1 ± 1 in the control group and 1 ± 9 in the PCa group (median ± IQR). Additionally, lifelong median ejaculation frequency was determined as 12 ± 5 for controls and 10 ± 4 for the PCa group. Inflammatory markers examined in serum and SII scores were observed to be statistically significantly increased in the cancer group. Conclusion: The sexual behavior and inflammatory parameters among patients with PCa diagnosis were identified to be significantly high compared to the control group and appear to be possible correctable risk factors. Informing men about sexual behavior from an early age and taking precautions for people at risk in the early period may be protective against this disease.